Description of the Quality of Life in Elderly at Nursing Home - Salsabila Fajari; Nina Sumarni; Adelse Prima Mulya (Indonesian Journal of Global Health Research, 2025)
The quality of life among the elderly is prone to decline due to physical, mental, and social deterioration. Assesing the quality of life in the elderly is essential to measure the effectiveness of care in nursing homes, ensuring that residents live safely and comfortable. This study aims to describe of the quality of life among the elderly at UPTD Pusat Pelayanan Sosial Griya Lansia (PPSGL) Ciparay. Method: This research is a quantitative descriptive study. The sample consisted of 60 elderly individuals selected using purposive sampling technique. Data were collected through the WHOQOL-OLD questionnaire which has been translated into Indonesian and has been tested for validity using the Rasch Model and its reliability with the results of the Cronbach's Alpha value of 0.75. Data were analysis using univariate analysis. The results showed that 55% of the elderly had a good quality of life, with 80% at a good level in the death and dying domain and 48.3% at a poor level in the sensory abilities domain. Good quality of life is something that needs to be maintained. However, almost half of the elderly at the UPTD Pusat Pelayanan Sosial Griya Lansia (PPSGL) Ciparay are at a poor level in the past, present and future activity and sensory abilities domain.